1973
DOI: 10.1172/jci107174
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Thyroid Hormones by Phagocytosing Human Leukocytes

Abstract: A B S T R A CT Thyroxine (T4) and triiodothyronine (T3) are rapidly degraded by a purified preparation of myeloperoxidase (MPO) and H202 with the formation of iodide and material which remains at the origin on paper chromatography. Deiodination by MPO and H202 occurs more readily at pH 7.0 than at pH 5.0 in contrast to iodination by this system which is known to occur more readily at pH 5.0 than at pH 7.0. Degradation is inhibited by azide, cyanide, ascorbic acid, and propylthiouracil. Methimazole stimulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The presumed mechanism was the conversion of T 4 to T 3 by PMNLs, freeing up iodide to kill micro-organisms (Klebanoff & Green 1973). Considering our results, that PTU pre-incubation had no specific effect on T 4 -induced O 2 production, we hypothesized that the source of halide for increased killing might be the thyroid hormone-induced halide incorporation into PMNLs.…”
Section: Resultsmentioning
confidence: 77%
“…The presumed mechanism was the conversion of T 4 to T 3 by PMNLs, freeing up iodide to kill micro-organisms (Klebanoff & Green 1973). Considering our results, that PTU pre-incubation had no specific effect on T 4 -induced O 2 production, we hypothesized that the source of halide for increased killing might be the thyroid hormone-induced halide incorporation into PMNLs.…”
Section: Resultsmentioning
confidence: 77%
“…Activated phagocytosing neutrophils are capable of cleavage of thyroxinebinding globulin (TBG), thus increasing the amount of extracellularly available T 4 (Jirasakuldech et al 2000). As mentioned previously, phagocytosing neutrophils also metabolize significant amounts of TH (Woeber 1971, Woeber et al 1972, Klebanoff & Green 1973, Woeber & Ingbar 1973. This suggests that TH metabolism plays an important role in infiltrating neutrophils during infection.…”
Section: Role Of Intracellular Thyroid Hormone Metabolism In Neutrophmentioning
confidence: 81%
“…Murine neutrophils contain the TH transporter MCT8, whereas human neutrophils express MCT10 but not MCT8 mRNA (Boelen et al 2005, van der Spek et al 2016. It has long been known that activated neutrophils are capable of deiodinating both T 3 and T 4 (Woeber 1971, Woeber et al 1972, Klebanoff & Green 1973, Woeber & Ingbar 1973. Research from the seventies already found that phagocytosing human neutrophils can generate both T 3 and rT 3 from T 4 and that this deiodinating activity was mainly present in the granule fraction of the cells (Woeber 1976(Woeber , 1978.…”
Section: Intracellular Thyroid Hormone Metabolism In Neutrophilsmentioning
confidence: 99%
See 2 more Smart Citations